Kepemimpinan, Budaya Organisasi, dan Stres Kerja Terhadap Kepuasan Kerja Karyawan pada Kantor Badan Pusat Statistik Wonogiri - Aldila Oktaprimurti; Ida Aryati Diyah; Istiatin Istiatin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The purpose of this study is to determine the influence of leadership, organizational culture, and work stress on employee work satisfaction at the Wonogiri Central Statistics Agency office. The method used is descriptive quantitative. The population used in this study was 49 employees of the Wonogiri Central Statistics Agency. The sampling technique used in this study was saturated sampling, a sampling technique where all members of the population are sampled. The analysis technique used was multiple linear regression analysis using SPSS version 25. Multiple linear regression analysis uses classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The F-test, hypothesis testing, and coefficient of determination (R2) tests were used to test the variables. This technique was used to obtain and utilize questionnaires. Data collection in this study used observation, documentation, questionnaires, interviews, and literature review. The results of the study indicate that leadership and organizational culture variables significantly influence employee work satisfaction at the Wonogiri Central Statistics Agency office. Meanwhile, work stress variables do not significantly influence employee work satisfaction at the Central Statistics Agency office.